Rancang Bangun Identifikasi Kehadiran Mahasiswa Otomatis Menggunakan Face Recognition dan Kartu Tanda Mahasiswa ( KTM ) Menggunakan Internet of Things (IOT) - Fazar Syahfitra; Akim Manaor Hara Pardede; Magdalena Simanjuntak (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
This study aims to design and develop an automatic attendance system using Radio Frequency Identification (RFID) technology and an ESP32 CAM. The system is designed to improve efficiency and accuracy in recording student attendance in academic environments. When a student's RFID card is scanned, the system automatically identifies the student and captures an image through the ESP32 CAM as additional proof of attendance. Attendance data and captured images are stored in a database that is connected in real-time via the Internet of Things (IoT). The results of the testing show that this system is able to perform the attendance process quickly and accurately, providing convenience for administrators in managing and monitoring attendance data digitally.